2010
DOI: 10.4102/hsag.v15i1.484
|View full text |Cite
|
Sign up to set email alerts
|

Retaining professional nurses in South Africa: Nurse managers’ perspectives

Abstract: South Africa is experiencing a serious shortage of nurses, which has to be addressed to prevent crises in health care services. Previous studies (Fletcher 2001:324; Oosthuizen 2005:117) found that nurses change their work environment due to dissatisfaction with their job situations. This implies that creating a favourable environment in the workplace situation could help retain professional nurses in their posts, implying that retention strategies should be effective.An exploratory, descriptive, contextual and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
1
50
0
1
Order By: Relevance
“…34 Extrinsic rewards and professional opportunities were the aspects of the job that were most commonly found to be dissatisfying by particpants in this study; other studies from Malawi and South Africa also found nurses to be dissatisfied with these particular subscales. [22][23][24] The findings in several of the previous studies reviewed 3,33,34,35 suggest moderate satisfaction among nurses, which is consistent with the findings of this study. These studies further suggest some satisfying and dissatisfying elements of the nursing profession across various cadres of nurses and cultures.…”
Section: Nurses' Job Satisfactionsupporting
confidence: 90%
See 1 more Smart Citation
“…34 Extrinsic rewards and professional opportunities were the aspects of the job that were most commonly found to be dissatisfying by particpants in this study; other studies from Malawi and South Africa also found nurses to be dissatisfied with these particular subscales. [22][23][24] The findings in several of the previous studies reviewed 3,33,34,35 suggest moderate satisfaction among nurses, which is consistent with the findings of this study. These studies further suggest some satisfying and dissatisfying elements of the nursing profession across various cadres of nurses and cultures.…”
Section: Nurses' Job Satisfactionsupporting
confidence: 90%
“…8,20,21 Such behaviours are associated with job dissatisfaction among nurses. [22][23][24] Patient and public complaints about the quality of nursing care in Malawi may be related to negative attitudes among nurses who are dissatisfied with their jobs. This study was conducted to investigate the relationship between nurses' job satisfaction and attitudes towards nursing care at Mzuzu Central Hospital in Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' plans to stay or leave were correlated to their control on work environment and availability of resources and equipment as the latter wasted their time and burned them out [27]. Multiple studies have shown correlation with control and responsibilities and job satisfaction, Mokoka et al [28] found a strong correlation with job satisfaction and intent to leave and unfair opportunities to job development [29,30] and noted a control over work included involvement in decision making and competency of work place and Takase et al [31] found that nurses were more satisfied and intended to stay when they were involved in the decision making to establish policies and patient education. These findings are in congruence with the finding of this study and support the strong correlation between job satisfaction and satisfaction with control and responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of care in the critical care units has also been affected. Nursing in South Africa finds itself in a crisis because of the impact of globalisation and increasingly porous country borders facilitating an increase in the exodus of skilled professional nurses, leading to a shortage of critical care nurses (De Beer, Brysiewicz, & Bhengu, 2011;Department of Health, 2012) and as nurse leaders, managers and the public opinion reveal poor standards of nursing care (Mokoka, Oosthuizen, & Ehlers, 2010;News24, 2013;Oosthuizen, 2012). Examples of concerns expressed by the Critical Care Nurses Forum (2013) and medical doctors include poor adherence to routine and evidence-based nursing care of critically ill patients and decreased accountability and responsibility as critical care nurses are not involved in monitoring and evaluating patient care.…”
Section: Introductionmentioning
confidence: 99%